TRADISI SOSIAL METANDA MALI’ DAN METUA’ PADA UPACARA KEMATIAN RAMBU SOLO’ DI TANA TORAJA - Enjelita Mardelin Mangape; Ferdinand Kerebungu; Veronika Salem (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2021)
The purpose of this study is to identify, describe and analyze the customary system of death of the Toraja Metanda Mali 'and Metua' tribes which strengthens brotherhood. This study uses qualitative research, using qualitative descriptive analysis techniques with interactive models Miles and Huberman, Sugiyono 2015. Results of the study shows that in the process of the social tradition of Metanda Mali' and Metua' at the funeral ceremony of Rambu Solo' in the Toraja community, especially in Lembang Lemo Menduruk, it is always considered a burden to the community because the care given is interpreted by the community as a form of debt that must be paid. Metanda Mali' is a form of care given by people who have no family relationship with the grieving person, Metua is a form of concern given by people who have family relations with the grieving person, in the Toraja language it is called “Rara Buku”. only focused on Metanda Mali' and Metua' as a burden without the community realizing that the tradition of Metanda Mali'and Metua' can strengthen brotherly relations.